THE ADAPTATION LEVEL OF ALFALFA (MEDICAGO SATIVA L.) THAT IRRADIATED WITH GAMMA RAYS ON A FIELD SCALE - I., Prihantoro,; A., Anandia,; A. T., Aryanto,; M. A., Setiana,; P. D. M. H., Karti, (Pastura, 2019)
Alfalfa (Medicago sativa L.) a high nutritious and palatability legume for ruminant. Constrain of alfalfa availability in Indonesia are due to the plant adaptability in tropical environment. Aim of the study was to measure the adaptation level of alfalfa that irradiated with gamma rays on a field scale. The study consisted of four types of plant sources, mutation plants with different gamma ray levels (0Gy, 200Gy, 300Gy and 400Gy). Plant tillers was analyzed with a complete randomized design with 3 replications, 20 plants per replication. Growth capability, leaf color, flowering time and pest attack level were analyzed descriptively. The results showed that alfalfa irradiated with 300 Gy significantly (p<0.05) produced highest tillers. Irradiated 300 Gy plant gave better result on growth capability, flowering capability, and number of not attack plant from pests. The higher level of gamma ray irradiation showed the changed in leaf color levels from dark green to light green. Keywords: alfalfa (Medicago sativa L.), mutation, gamma ray irradiation, field scale